MAX phases : properties of machinable ternary carbides and nitrides - Barsoum, M. W. (Wiley-VCH, 2013)
In this comprehensive yet compact monograph, Michel Barsoum, one of the pioneers in the field and the leading figure in MAX phase research, summarizes and explains, from both an experimental and a theoretical viewpoint, all the features that are necessary to understand and apply these new materials. In so doing, he covers elastic, electrical, thermal, chemical and mechanical properties in different temperature regimes, concluding with a treatment of MAX phase composites and potential as well as current applications.